Amérique Septentrionale. - Desbuissons, E., b. 1827 (Migeon, 1867)
Map shows major cities and notable physical features for North America; "Territoire D'Alaska," "Nouvelle Bretagne" [Canada], Groenland, the United States, Mexico, Central America, and the Antilles; areas of Native American habitation; coloration of U.S. Mexico boundary line along Gila River with 1848 treaty note; transcontinental railroad line from New York to San Francisco; "Oregon" label is north of 1846 U.S. northern boundary and "Columbia" label is on the south side. Inset: "Chute du Niagara, [by] Fréderic Legrip del." Relief shown by hachures. Scale not given.